Dieter Felix Gerhardt: A Case Study of Russian Espionage in South Africa - van Aswegen, Henning (Scientia Militaria - South African Journal of Military Studies, 2023)
My contestation in this research article is that Dieter Felix Gerhardt, a South African naval officer based in Simon’s Town, was a paid penetration agent for the Russian Military Intelligence Service, Glavnoje Razvedyvatel’noje Upravlenije, in the South African Defence Force. This contestation cannot be accepted as true without due scientific investigation and analysis by way of a case study as my primary research method. For this case study on Dieter Felix Gerhardt and his wife, Ruth Johr, exploratory research was not necessary or attempted, because the phenomena of espionage, intelligence services, and counterintelligence exist in sovereign countries (mostly by way of legislation), as elements and instruments of government structures and policy. The case study on Dieter Felix Gerhardt and Ruth Johr was approached from the perspective of intelligence studies; therefore, the intelligence terminology and nomenclature used will be defined, explained, and referenced.